Significance of hysteroscopy in diagnosis and treatment of congenital uterine anomalies - Šaranović, Milena S; Matejić, Suzana; Matejić, Nebojša; Radić, Ivan; Trajković, Goran (Vojnosanitetski pregled, 2020)
Background/Aim. Hysteroscopy is one of the important methods in the endoscopic diagnosis and treatment of infertility, particularly at the examination of the morphology and function of the uterus. Uterine factor is present at 10% of infertile women, in which changes of the uterus can be congenital or acquired. The aim of this study was to estimate the significance of hysteroscopy in the diagnosis and treatment of congenital anomalies of the uterine cavity in patients in whom there was a reasonable suspicion for them based on prior clinical, ultrasound and hysterosalpingography (HSG) findings. The significance of hysteroscopy is considered in relation to the number of pregnancies achieved depending on the malformations in the 12 months period after the completion of the diagnostic or operational hysteroscopy. Methods. The study included 176 patients with congenital uterine anomalies, which had undergone hysteroscopy, diagnostic or operative, in the period from January 1, 2013 till January 1, 2016. Percentage of pregnancy was followed at all patients during the first 12 months after surgery. Patients were divided into two groups: the first group contained women who had pregnancy, and the second group included women who earlier were not pregnant. Their characteristics were compared, such as: age, duration of infertility, previous pregnancy and/or pregnancy loss, HSG and ultrasound findings, types of congenital anomalies, type of hysteroscopy, as well as the existence of associated pathology. Results. The mean age of patients tested in the study was 35 years. The group of patients with primary infertility had a total of 107 patients, while 69 patients were with secondary infertility. The average duration of infertility was 3 years in the studied patients. In the 12-months period, 39 of the examined women began pregnancy, which was completed with term delivery in 33 women. χ2 test showed a statistical significance difference (p < 0.05) between the groups of the patients with or without pregnancy after hysteroscopy in relation to infertility types as well as in relation to the number of previous miscarriages. Conclusion. Subseptus and septus uteri were the most common congenital uterine malformations in our patients. Very rare were uterus arquatus, uterus unicornis and uterus bicornis. In our study, 1/5 of examined women achieved pregnancy after hysteroscopy in the reporting period of 12 months, while the majority of these pregnancies ended with term delivery. The percentage of miscarriages in the examined women was reduced from 38% to 15% after hysteroscopy. In women who achieved pregnancy, uterine septum and subseptum were mostly diagnosed and in these patients hysteroscopic resection was successfully performed.